INCLUSIVE LIBRARY FOR IMPAIRED STUDENTS IN VIETNAMESE UNIVERSITY (LIS TODAY, 2024)
As one of the first-hand empirical efforts, the paper investigates the outstanding role  of the inclusive library formed in the university, examines how they work, structure, and its  impacts on cultivating accessibility of students with disabilities. Particularly, the article  emphasizes equality rights, policy reforms, and opportunities for approaching institutions of  higher education, as well as identifies the practical situations existing. Along with that, an  empirical observation was carried out with over 100 websites of libraries in Vietnamese  universities including public and private institutions. The findings of the investigation show  that the inclusive library contributes significantly to the overall development of people with  disabilities, especially in gaining equal accessibility to benefits, rights, policies, and  opportunities from society. As a consequence of the state of current existing situations, which  directly intervene in the special needs of learners with impairments, the paper makes some  recommendations for libraries of Vietnamese universities, such as facilities, library  infrastructure, collections and services, activities, etc. Moreover, these practical solutions to  practical problems aim to raise further awareness among the government, leaders of parent  universities, staff, and non-disabled people with respect to the equal rights and policies of  impaired students, regardless of what conditions and where they are. More importantly, they  have many more equal opportunities for improving and developing comprehensively their  impaired abilities and skills in certain circumstances. Theoretical and practical situations of  the findings are considered below.
Keywords: Inclusive library; people with disabilities; Vietnamese University; recommendations